TECHNOLOGY FOR OBTAINING KNITTED FABRICS FROM VARIOUS RAW MATERIALS - Rahmatova, Sadoqat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The textile and clothing and knitwear industry occupies a leading place in the world. The production of textile and garment and knitwear products is increasing day by day, the reason for this is the increase in the level of consumption on a global scale.